DSM-5 MALADAPTIVE TRAITS, PERSONALITY AND SOCIODEMOGRAPHIC VARIABLES: PREDICTIVE DIMENSIONAL MODELS IN A PORTUGUESE CLINICAL SAMPLE - Henriques-Calado, J.; Gonçalves, B.; Pires, R.; Paulino, M.; Gama marques, J.; Marques, C. (19th WPA World Congress of Psychiatry, 2019)
Objectives: To examine the relations among contemporary models of pathological and normal-range personality traits in a clinical sample, with emphasis on sociodemographic variables. Background: The alternative dimensional classification for personality disorders in DSM-5 may be reliably assessed using the Personality Inventory for DSM-5 (PID-5). Empirical evidence suggests a shared structure with the Five-Factor Model (FFM) of general personality. Although there is a growing body of literature on the PID-5, its relationships with sociodemographic variables in clinical samples are still largely understudied. This study aims to: test models that predict each PID-5 dimension based on FFM traits and sociodemographic data (age, sex, schooling). Materials and Methods: A cross-sectional study of a psychiatric outpatient sample of 207 participants aged between 18 and 68 years (Mage = 43.62, SD = 11.04), mainly male (71%), with an average of 10 years schooling (SD = 4.47). Self-reported assessment: PID-5; FFM Inventory. Five multiple linear regressions were computed. Results and Conclusions: High FFM Neuroticism and low schooling predicted PID-5 Negative Affectivity, explaining 94% of the variance (R-squared = .94); low FFM Extraversion and high age predicted PID-5 Detachment (R-squared = .88); low FFM Agreeableness and male sex predicted PID-5 Antagonism (R-squared = .82); low FFM Conscientiousness and low schooling predicted PID-5 Disinhibition (R-squared = .82); high FFM Openness predicted PID-5 Psychoticism (R-squared = .83). Normal-range personality and sociodemographic variables predict DSM-5 maladaptive traits in a conceptually coherent manner. More research is required in clinical samples. Analyses strengthen the Zeitgeist for using broad dimensions that span normative and pathological functioning.